Insights Into Antimicrobial Resistance From Dental Students in the Asia–Pacific Region - Saba Ghafoor; Gabriela Salvadori; Shiho Kino; Vy Thi Nhat Nguyen; Tam Thi-Thanh Nguyen; Miho Ishimaru; Antônio Pedro Ricomini-Filho; Cassiano Kuchenbecker Rösing; Dileep De Silva; Jun Aida; Belinda Farias Nicolau; Ratilal Lalloo; et al. (International Dental Journal)
Background: Dentists, as prominent prescribers, are key stakeholders in addressing the antimicrobial resistance (AMR) crisis. Dental students’ perceptions about the topic have been underexplored in the Asia–Pacific region, a key location for the development and spread of AMR. Thus, the aim of this study was to evaluate the awareness and confidence to prescribe antimicrobials amongst dental students studying in the region. Methods: Students from 15 dental schools in 4 countries were invited to participate in a cross-sectional online survey during 2022–2023. A previously validated and standardised 14-item instrument was utilised. Results: In all, 1413 responses were collected from Australia (n = 165), Sri Lanka (n = 112), Japan (n = 173), and Vietnam (n = 963). Of those, 201 were from final-year students (14.2%). On a scale from 1 to 10, awareness on AMR was placed at a mean (SEM) priority of 8.09 (0.05). With regards to target areas to address for mitigation of the AMR crisis, participants placed general public awareness at the top (mean [SEM] 8.53 [0.05]). Final-year students presented a mean (SEM) level of confidence to prescribe antibiotics of 6.01 (0.14) on a scale from 1 to 10, whilst 59.7% and 56.8% indicated feeling pressured to prescribe by patients or when lacking time, respectively. Final-year students participating in research activities assigned a higher priority to AMR compared to their peers not involved in research (mean [SEM] 8.6 [0.19] vs 7.81 [0.16]; P = .01). Conclusions: This study highlights a need for increased awareness and confidence to prescribe amongst dental students in the Asia–Pacific region, an understudied population thus far. To mitigate this issue, the implementation (followed by assessment) of local educational and antibiotic stewardship initiatives is warranted.